Zone 2 sacral fractures managed with partially-threaded screws result in low risk of neurologic injury. Issue 7 (July 2016) - Herman, Amir; Keener, Emily; Dubose, Candice; Lowe, Jason A.
Abstract: Background: Zone 2 sacral fractures account for 34% of sacral fractures with reported neurological deficit in 21−28% of patients. The purpose of this study was to examine the risk factors for neurological injury in zone 2 sacral fractures. The authors hypothesized that partially thread iliosacral screws did not increase incidence of neurologic injury. Methods: A retrospective review of consecutive patients admitted to a level 1 trauma center with zone 2 sacral fractures requiring surgery from September 2010 to September 2014 was performed. Patients were excluded if no neurologic exam was available after surgery. Fractures were classified according to Denis and presence/absence of comminution through the neural foramen was noted. Fixation schema was recorded (sacral screws or open reduction and internal fixation with posterior tension plate). Any change in post-operative neurological exam was documented as well as exam at last clinic encounter. Results: 90 patients met inclusion criteria, with zone 2 fractures and post-operative neurological exam. No patient with an intact pre-operative neurologic exam had a neurological deficit after surgery. 86 patients (95.6%) were neurologically intact at their last follow-up examination. Four patients (4.4%) had a neurological deficit at final follow-up, all of them had neurological deficit prior to surgery. 81 patients were treated with partially threaded screws of which 1 (1.2%) had neurological deficit at final follow-up. Fifty-seven fractures (63.3%) were simple fractures and 33 fractures (36.7%) were comminuted. All four patients with neurological deficit had comminuted fractures. The association between neurologic deficit in zone 2 sacral fracture and fracture comminution was found to be statistically significant ( p -value = 0.016). No nonunion was observed in this cohort. Conclusions: The use of partially threaded screws for zone 2 sacral fractures is associated with low risk for neurologic injury, suggesting that compression through the fracture does not cause iatrogenic nerve damage. The low rate of sacral nonunion can be attributed to compression induced by the use of partially threaded compression screws. There is a strong association between zone 2 comminution and neurologic injury.